The use of hyaluronic acid fillers in patients with autoimmune endocrinopathies; in particular, women with Hashimoto’s disease – hints for aesthetic doctors - Katarzyna Bornikowska; Paweł Kubik; Wojciech Zgliczyński (Menopause Review)
The increase of the incidence of autoimmune diseases and, at the same time, a significant surge in the number of regenerative/anti-aging medicine treatments carried out, raises the need to systematise the current knowledge on the safety of the use of hyaluronic acid fillers in patients with autoimmune diseases and to frame management guidelines for aesthetic doctors. One of the most prevalent autoimmune diseases is chronic lymphocytic thyroiditis, so-called Hashimoto’s disease, which affects one in every 5–10 women who visit a regenerative medicine doctor. Women in the perimenopausal and menopausal period, aged 40–54 years, were the single largest target group for aesthetic treatments. At the same time, Hashimoto’s disease, similarly to other autoimmune disorders, constitutes a contraindication to most treatments with hyaluronic acid fillers and biostimulators. Due to the dysfunction of the immune system in this group of patients, there is a higher risk of adverse side effects, especially those of immunological nature. Based on the available literature, the incidence of adverse reactions after the use of hyaluronic acid-based fillers amounts to 0.01–1% and is undoubtedly underestimated. The most typical one is recurrent oedema and granulomas. The following paper reviews the existing literature on the safety of hyaluronic acid fillers in patients with autoimmune endocrinopathies.